2017
DOI: 10.1037/abn0000265
|View full text |Cite
|
Sign up to set email alerts
|

Increased startle potentiation to unpredictable stressors in alcohol dependence: Possible stress neuroadaptation in humans.

Abstract: Stress plays a key role in addiction etiology and relapse. Rodent models posit that following repeated periods of alcohol and other drug intoxication, compensatory allostatic changes occur in the central nervous system (CNS) circuits involved in behavioral and emotional response to stressors. We examine a predicted manifestation of this neuroadaptation in recently abstinent alcohol dependent humans. Participants completed a translational laboratory task that uses startle potentiation to unpredictable (vs. pred… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 87 publications
(149 reference statements)
0
34
0
Order By: Relevance
“…In two independent samples, our lab found that greater levels of current problematic alcohol use (e.g., binge drinking) were associated with greater aversive reactivity to U-threat, measured via startle eyeblink potentiation (Gorka et al, 2016a). Recently, Moberg et al (2017) replicated and extended the findings in Gorka et al (2016a) by demonstrating that individuals with current alcohol dependence displayed greater startle potentiation to U-threat, but not P-threat, compared with controls. In a separate sample of panic disorder patients, it was similarly shown that individuals with remitted alcohol dependence displayed greater startle potentiation to U-threat, but not P-threat, compared with individuals with no lifetime diagnosis of alcohol use disorder (AUD; Gorka et al, 2013).…”
Section: Introductionmentioning
confidence: 64%
“…In two independent samples, our lab found that greater levels of current problematic alcohol use (e.g., binge drinking) were associated with greater aversive reactivity to U-threat, measured via startle eyeblink potentiation (Gorka et al, 2016a). Recently, Moberg et al (2017) replicated and extended the findings in Gorka et al (2016a) by demonstrating that individuals with current alcohol dependence displayed greater startle potentiation to U-threat, but not P-threat, compared with controls. In a separate sample of panic disorder patients, it was similarly shown that individuals with remitted alcohol dependence displayed greater startle potentiation to U-threat, but not P-threat, compared with individuals with no lifetime diagnosis of alcohol use disorder (AUD; Gorka et al, 2013).…”
Section: Introductionmentioning
confidence: 64%
“…However, neuroadaptation following chronic anxiety may change the nature of these responses and underlying neurocircuits over time. Consistent with this view, while studies generally show increased defensive reactivity and increased amygdala activity in pathological anxiety (66,118), instances of hypo-reactivity in patients are not infrequent (119,120). The current interpretation of these opposing effects is that they reflect distinct symptoms.…”
Section: Step 4: Mechanisms Of Pathophysiologymentioning
confidence: 82%
“…The current startle findings are consistent with prior studies examining reactivity to U‐threat in relation to AUD and drinking behaviors. In four separate samples, it has been shown that heavy drinkers and individuals with AUD display increased startle to U‐threat compared with healthy controls and individuals with anxiety disorders. It has also been previously demonstrated that startle magnitude to U‐threat correlates with AUDIT scores and self‐reported drinking problems .…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, it is important to understand whether behavioral and brain measures of U‐threat reactivity actually map onto the severity of AUD illness as well as negative reinforcement processes such as drinking to cope with negative affect. To date, two studies have shown that greater self‐reported alcohol problems were related to greater startle potentiation to U‐threat . It is important to extend this line of work to include U‐threat measures beyond just startle.…”
Section: Introductionmentioning
confidence: 99%